A Systematic Process for Functional Decomposition in the Absence of Formal Requirements. Issue 1 (13th September 2016) - Brimhall, Erika; Wise, Richard; Simko, Ryan; Huggins, John; Matteson, Whit
Abstract: A systematic approach is needed for developing implementation‐agnostic functional decompositions in the absence of formal requirements. This paper introduces a process for producing robust functional decompositions that provide full coverage of system functionality, enable consistency throughout the system architecture, and promote reusability of functions. The process uses activity diagrams to provide precise semantics, and defines concepts that support the development of robust implementation‐agnostic functional decompositions. The process has been successfully demonstrated through the functional decomposition of avionics software.